POLA TANAM DAN KONTRIBUSI AGROFORESTRI BERBASIS KELAPA DI HALMAHERA UTARA - Lewerissa, Ebedly (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The coconut-based agroforestry system in North Halmahera has been developing for a long time, but in its development some people still plant coconuts in monoculture. The purpose of this study was to determine the planting patterns developed in North Halmahera Regency and to determine the contribution of coconut-based agroforestry in North Halmahera. The method used was purposive sampling to determine the location of the study, a questionnaire to obtain social data and the analysis tool to calculate the feasibility of agroforestry businesses was financial analysis (BCR, NPV and IRR). The results showed that coconut-based land ownership in North Halmahera Regency was dominated by coconut monoculture patterns with a percentage of 80.56%. The application of coconut-based agroforestry planting patterns in North Halmahera Regency is three planting patterns, namely monoculture coconut planting patterns, mixed coconut planting patterns with nutmeg and mixed coconut planting patterns with nutmeg mixed with food crops and horticultural crops. The contribution of coconut-based agroforestry in North Halmahera Regency with an IRR value for coconut monoculture planting patterns of 48%, a coconut planting pattern mixed with lime nutmeg with an IRR value of 77% and a coconut planting pattern mixed with nutmeg mixed with food crops and horticulture with an IRR value of 117%. Therefore, it is necessary to pay special attention to the relevant agencies for the development of agroforestry planting patterns based on coconut mixed with nutmeg mixed with food crops and horticulture in the future